Battered Women Syndrome as a Theoretical Explanation of Domestic Violence (Journal of Asian Development Studies, 2023)
This study delves into the escalating issue of violence against women in Pakistan, focusing on Intimate Partner Violence (IPV) and its profound impact on battered women. They are centered in district Okara. Domestic violence is an important area of investigation for social scientists and an important point of concern in Pakistan. The study used a quantitative research approach, gathering empirical data from 209 responses of women, comprising 105 rural victims and 104 urban women fearing their male partners. The researcher applied purposive sampling and snowball technique to identify the current study participants. Findings reveal a higher prevalence of violence among rural women, particularly those with limited education. The study underscores the psychological and physical toll on victims, manifesting in posttraumatic stress disorder (PTSD), depression, anxiety, and physical injuries. The pervasive atmosphere of fear, where women feel akin to robots, lacking protection and living as prisoners, is illuminated. Additionally, the research explores the potential ramifications for children exposed to such violence. This comprehensive analysis aims to contribute valuable insights to the understanding of IPV dynamics, advocating for targeted interventions to safeguard the well-being of battered women in Pakistan.